SELECTIVE INHIBITION OF PAF-INDUCED HUMAN PLATELET AGGREGATION BY GARLIC - Saeed, Sheikh Arshad; Imran, (Journal of Research (Science), 2025)
Garlic exudate (0.2-2.5 mg) prepared by squeezing fresh garlic cloves inhibited platelet aggregation induced by platelet activating factor (PAF) in a dose-dependent manner. No inhibition of aggregation was observed when adenosine-5-diphosphate (ADP) or arachidonic acid (AA) were used as aggregating agents. This selective effect of garlic against PAF-induced aggregation was also seen with aqueous or alcoholic garlic extracts. These results suggest that PAF antagonists are present in garlic.